The Effect of Strategic and Directive Leaderships on School Leader’s Performance - I Made Sila; I Made Sutika; I Made Astra Winaya; I Nengah Sudiarta; I Gede Sujana; Ida Bagus Rai (Jurnal Pedagogi dan Pembelajaran, 2023)
School leaders have a number of roles that should be played together, including educators, managers, administrators, supervisors, motivators, entrepreneurs, and leaders. The role of school leaders as leaders and as instructional leaders specifically.This study aims to analyses the correlation between strategic and directive leadership on school leaders performance. The analysis used is a qualitative approach with a correlation design. This research was conducted using a survey method. The population in this study was the leader staffs (head and deputy head) of schools from kindergarten to high school/vocational school. The samples were taken from all existing leaders. The method used was regression and correlation as well as a significance test with the F test and the coefficient of determination (R2). The population in this study were the leadership staff (heads and deputy heads) of schools starting from kindergarten to high school/vocational school. The sample/population was taken from all the existing leaders, as many as 18 people.  This study also used interview and questionnaire techniques, namely holding questions and answers with representative sources to answer problems in the field (school). The analysis used is a qualitative approach with a correlation design. The results of the study showed that Strategic and directive leaderships have a significant effect on the school leader’s performance. Strategic leadership has a stronger influence on leadership performance, while directive leadership has a weaker influence.